2018
DOI: 10.1590/s1678-9946201860073
|View full text |Cite
|
Sign up to set email alerts
|

Renal dysfunction in Leishmaniasis and Chagas disease coinfection: a case report

Abstract: Visceral leishmaniasis (VL) is an endemic parasitic disease frequently found in Northeast Brazil and may cause acute kidney injury (AKI) and glomerulonephritis. After appropriate treatment, renal function recovery may occur. We describe the rare case of a patient with VL, who developed severe AKI requiring dialysis and was subsequently diagnosed with Chagas disease coinfection. After specific treatment for VL, there was partial recovery of the renal function, followed by the onset of Chagas disease cardiomyopa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 9 publications
(11 reference statements)
0
4
0
Order By: Relevance
“… 30 However, the present study is not incongruous with studies conducted by Efstratiadis et al and Alcântara et al, which reported a high level of serum urea for VL patients. 24 , 27 The difference may be attributed to the duration of dehydration (with an environmental difference), diet and severity of infection. 31…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“… 30 However, the present study is not incongruous with studies conducted by Efstratiadis et al and Alcântara et al, which reported a high level of serum urea for VL patients. 24 , 27 The difference may be attributed to the duration of dehydration (with an environmental difference), diet and severity of infection. 31…”
Section: Discussionmentioning
confidence: 99%
“…Our finding revealed that the mean serum creatinine level which was found significant increase in VL patients compared to healthy controls is in corroboration with the previous studies conducted on renal function profile among VL cases, and reported AKI and progressive glomerulonephritis found an increase in serum creatinine level. [24][25][26] This may be attributed to the level of immune complex deposition, T cells and adhesion molecule activation during the inflammatory processes observed in active VL disease resulting in renal dysfunction. 27,28 The production of reactive oxygen species (ROSs) from the activated macrophage may also contribute to the alterations of renal function.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…L. mexicana causes cutaneous leishmaniasis (CL) and is endemic to Texas (Gustafson et al 1985, Barnes et al 1993, McHugh et al 1995, Wright et al 2008, Trainor et al 2010, but cross-reaction on Kalazar Detect Rapid Test with CL species is unlikely in both humans and dogs (Lemos et al 2008, Molinet et al 2013. Two additional dogs had positive rapid test results and were considered crossreaction with T. cruzi antibodies, but alternatively could be coinfected with T. cruzi and Leishmania spp., which have been found in dogs, humans, and wildlife (Alcântara et al 2018, de Oliveira Porfirio et al 2018, Viettri et al 2018.…”
Section: Posmentioning
confidence: 93%
“…The presence of viable Leishmania parasites in the urine of infected individuals is documented [120][121][122]. The crossing of the glomerular barrier by Leishmania is thought to be a consequence of VL renal lesions and renal failure [123,124]. Tubulointerstitial involvement and glomerulonephritis are the main causative agents of the proteinuria disorder, which is common in most patients with a clinical episode of leishmaniasis [125][126][127].…”
Section: Urinementioning
confidence: 99%